Les conceptions de l’identité sexuelle, le postmodernisme et les textes littéraires - Boisclair, Isabelle; Saint-Martin, Lori (Recherches féministes, 2006)
Le présent article trace d’abord un bref portrait de trois conceptions dominantes de l’identité sexuelle : le modèle patriarcal, le modèle féministe et le modèle postmoderne. Puis, après avoir présenté plus longuement le dernier, il analyse deux romans relayant cette conception postmoderne de l’identité de sexe/genre, l’un écrit par un homme (Self, de Yann Martel, paru en 1996), et l’autre par une femme (Ce qu’il en reste, de Julie Hivon, paru en 1999). Dans ces deux romans, qui revêtent de ce fait une importante dimension politique, les identités figées sont mises à mal tant discursivement que formellement - par la déconstruction des signes du passé et la mise en place de dispositifs énonciatifs confondant hommes et femmes, par exemple. Ils participent ainsi à une conception culturaliste de l’identité sexuelle, selon laquelle le genre est une performance.,This article begins by briefly introducing three major frameworks for conceptualizing gender identity : a patriarchal model, a feminist model and a postmodern model. After exploring the third in greater depth, it offers a reading of two novels of postmodern gender identity, one by a male author (Self by Yann Martel, 1996), one by a female author (Ce qu’il en reste by Julie Hivon, 1999). Both novels, which are therefore strongly political, challenge the concept of predetermined gender identity on the levels both of discourse and of form, by deconstructing older concepts and by blurring gender lines. They are therefore grounded in a view of gender identity as cultural construction and performance.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; fem1000; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; études littéraires

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Section: 1 vol. (XIX-564 p.) ; 24 x 19 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Nous, enfants d'homos homoparentalité: une génération témoigne - Kaim, Stéphanie (Éd. de La Martinière, 2006)
A partir d'une enquête menée en France et en Californie, l'auteure décrit les conditions d'accession à l'homoparentalité, depuis le milieu des années 1970. Elle donne la parole à de jeunes adultes élevés par des homosexuels pour mieux poser la question de l'éducation et de l'orientation sexuelle de ces enfants.
Section: 1 v. (171 p.) : couv. illustrations en coul. ; 19 cm
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; californie; cours; discipline; europe; filiation; france; identités LGBTQIA2+; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; shm4000; thématiques; états-unis

The transgender studies reader - Stryker, Susan; Whittle, Stephen (Routledge, 2006)
Although the term "transgender" itself has achieved familiarity only within the past decade, this authoritative collection of articles demonstrates that the study of behaviors, bodies, and subjective identities which contest common Eurocentric notions of gender has a history stretching back at least to the early 20th century. Transgender studies is the latest area of academic inquiry to grow out of the exciting nexus of queer theory, feminist studies, and the history of sexuality. Because transpeople challenge our most fundamental assumptions about the relationship between bodies, desire, and identity, the field is both fascinating and contentious. The Transgender Studies Reader puts between two covers fifty influential texts with new introductions by the editors that, taken together, document the evolution of transgender studies in the English-speaking world. By bringing together the voices and experience of transgender individuals, doctors, psychologists, and academically-based theorists, this volume will be a foundational text for the transgender community, transgender studies, and related queer theory.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; interdisciplinarité; occident; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis